Efeitos do Fipronil e/ou Glofosato sobre comportamento do Zebrafish (Danio rerio) - Chaulet, Fabiele da Costa (2018)
The common use of pesticides has been causing serious consequences for non-target organisms. Widely used in many environments - agriculture and domesticated animals, it has been accumulating in many environments and potentially dangerous for non-target organisms that are exposed. In aquatic environments, the incidence of several pesticides has been proven, being found associated or separated depending on the collection season. Among the most commonly used agrochemicals are the products with active ingredient Glyphosate, a non-selective herbicide, indicated for the control of weeds in all crops, such as pre-dessication prior to planting or post emergence of the crop, and the other product is Fipronil, whose indication is for pest control. It is widely used in seed treatment and aerial applications for pest control and in home environments for flea and tick control. The half-life of these products is between 1 day, and can arrive for 1 year in the environment in which it was used. Because of this, aquatic organisms can be exposed to one or more different types of pesticides, raising the question that their association might or might not enhance the behavioral effects of these organisms. Based on this assumption, adult zebrafish fish were exposed to the products Glyphosate and Fipronil, isolated and associated and tested in an apparatus, where behavior was evaluated to a new environment. As its behavior is well defined in other studies, some behavioral parameters such as residence time between segments (bottom, middle and top), mean velocity, number of rotations, angle of turn were selected, which served as a basis to analyze the consequences of these contaminations. The concentrations of the products used were determined based on the morphological and behavioral changes described in the literature. These analyzes showed that the isolated products alter the behavior, occurring a potentiation in the results when associated and some parameters not relevant before, with the association of the products had significant alterations.